An Analysis of Verb Usage in Narrative Texts in 10 Bible Character Stories for Sunday School Children - Sanggam Siahaan; Miranda Kristin Lumban Tungkup; Sarah Priscilla Silitonga; Esra Delima Hutabarat; Rimtahi Bahtra V. Marbun; Dwi Angeli Pardede; Ummi Kalsum Siahaan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study analyzes verb usage in ten Bible character stories designed for Sunday school children, with a specific focus on how various types of verbs contribute to narrative structure and character portrayal. Utilizing a qualitative research design, the study categorizes verbs into four types: transitive, intransitive, inchoative, and stative (e.g.,